Pendampingan Literasi Digital Siswa MTs dalam Pemanfaatan Media Pembelajaran Digital - Danissatun Sakdia; Choirun Nisa’; Lailatun Nufus; Sinta Ma’sumah; Nur Wiji Sholikin (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
Digital literacy is a crucial competency for students to navigate technological developments in education. The use of digital learning media in Islamic junior high schools (MTs) still faces various challenges, particularly limited student understanding and skills in using digital media optimally and responsibly. This community service activity aims to improve MTs students' digital literacy through mentoring in the use of digital learning media. The approach used was participatory, with stages including outreach, training, and direct mentoring. Data collection techniques included observation, interviews, and documentation, while data analysis employed a qualitative descriptive approach. The results of the activity indicate an increase in students' understanding and skills in utilizing digital learning media independently, as well as an increased awareness of the ethics of digital media use. This digital literacy mentoring is expected to support improvements in the quality of learning and build a sustainable digital literacy culture within the madrasah environment.